HEMATOPOIETIC STEM CELL TRANSPLANTATION IN CHILDREN WITH HEMOGLOBINOPATHIES: BRAZILIAN SOCIETY OF BONE MARROW TRANSPLANTATION CONSENSUS - Darrigo Junior, Luiz Guilherme; Mello Costa, Thalita Cristina; Vieira, Ana Karine; Albino, Cintia Delbem; Navarro Barros, George Maurício; Garcia, Julia Lopes; Rigolin Fortunato, Laila; Souza Santos, Flavia Leite; Fonseca, Guilherme; Guerino-Cunha, Renato Luiz; Cunha De Santis, Gil; Pinto Simões, Belinda (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2021)
THE BRAZILIAN SOCIETY FOR BLOOD AND MARROW TRANSPLANTATION (SBTMO) PRESENTS THE BRAZILIAN GUIDELINES ON HEMATOPOIETIC STEM CELL TRANSPLANTATION FOR CHILDREN WITH HEMOGLOBINOPATHIES